The Regionalization of Ventral Hernia Repair: Occurrence and Outcomes over a Decade. Issue 7 (July 2013) - Colavita, Paul D.; Walters, Amanda L.; Tsirline, Victor B.; Belyansky, Igor; Lincourt, Amy E.; Kercher, Kent W.; Sing, Ronald F.; Heniford, B. Todd
Ventral hernia repairs (VHRs) have always been considered standard general surgery cases. Recently, there has been a call for "Centers of Excellence." We sought to investigate outcomes and trends between high- and low-volume centers. The Nationwide Inpatient Sample (NIS) data were analyzed from 1998–1999 (T1) and 2008–2009 (T2) for all VHRs. Hospitals were stratified into high-, medium-, and low-volume centers (HVC/MVC/LVC). Demographics, comorbidities, and outcomes were compared. Surgical cases totaled 22, 771 in T1 and 37, 044 in T2. In T1, 34.3 per cent were performed in HVC versus 64.2 per cent in T2 ( P < 0.0001). LVC cases decreased between eras: 32.6 versus 16.1 per cent ( P < 0.0001). Comorbidities and emergent admissions increased with time ( P < 0.0001). Mortality was similar in both eras and between volume centers. Length of stay was less in LVC in T2 only (4.2 vs 4.8 days, P < 0.0001). Total charges were higher in HVCs in both eras ( P < 0.0001). These remained significant in T2 in multivariate regression (MVR). Hospital volume was not associated with most complications or death in either era with MVR. Charlson comorbidity score, age, and emergent admission were predictors of complications and death. Regionalization has occurred for VHRs. However, most complication and mortality rates are unrelated to volume and are linked to comorbidities, age, and emergencies.